Branding Dan Positioning Identitas Budaya Indonesia Dalam Pesan Iklan TV Komersial Bejo Bintang Toedjoe Jahe Merah - Agus Hermanto; Sa'diyah El Aldawiyah (UMSU, 2020)
Advertising messages can be a tool that represents what has been determined by the manufacturers in communicating marketing objectives. The purpose of this research is to find out how the visual form, narrative branding and positioning of Indonesian cultural identity in BEJO Bintang Toedjoe Masuk Angin Jahe Merah TV commercial messages. The method used in this study is a qualitative method with narrative analysis. The data collection technique used is the method of in depth interviews verbally and directly with several informants. The findings of this study in general BEJO Bintang Toedjoe's Masuk Angin jahe merah branding narratives are not yet strong, as a brand with a natural and modern personality and educational facilities about red ginger as a more nutritious spice. The narrative of positioning is not yet focused and the distinct differentiation is not yet clear as a statement, from red ginger which is processed in a modern and effective manner and quickly relieves the symptoms of colds in the first tube packaging in Indonesia.